Bulk Flotation of Low Grade Refractory Sulfide Lead-Zinc Ore - Güler, E. (Asian Journal of Chemistry, 2011)
In this research, bulk flotation from a low-grade refractor lead-zinc ore containing 3.5 % Zn and 1 % Pb and 1.9 % Fe was studied. Due to the problems involving sequential flotation of finely disseminated lead-zinc sulfide ore, the production of bulk lead-zinc concentrate was practiced. Flotation parameters such as activator (CuSO4) dosage, collector type [potassium amyl xanthate, sodium isopropyl xanthate] and dosage, flotation time, particle size and pH were investigated. Experimental results showed that collector dosage was the most significant factor affecting Zn and Pb recoveries. In the bulk flotation stage where 100 g/t CuSO4 and 150 g/t potassium amyl xanthate were used (at pH 8 and 10 min flotation time) maximum Zn and Pb recoveries were obtained as 94 and 83 %, respectively.